2021
DOI: 10.1101/2021.07.06.451152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irisin stimulates the release of CXCL1 from differentiating human subcutaneous and deep-neck derived adipocytes via upregulation of NFκB pathway

Abstract: Thermogenic brown and beige adipocytes play an important role in combating obesity. Recent studies in rodents and humans have indicated that these adipocytes release cytokines, termed "batokines". Irisin was discovered as a polypeptide regulator of beige adipocytes released by myocytes, primarily during exercise. We performed global RNA sequencing on adipocytes derived from human subcutaneous and deep-neck precursors, which were differentiated in the presence or absence of irisin. Irisin did not exert an effec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…It has been shown that IL-6 released by differentiation of human beige adipocytes promotes the browning of fat (Kristóf et al, 2019). Moreover, irisin promotes the release of CXCL1 stimulated by human subcutaneous and neck differentiated adipocytes through upregulation of the NF-κB pathway (Shaw et al, 2021). However, whether the increase in IL-6 and CXCL1 in mothers has an effect on offspring adipocytes needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IL-6 released by differentiation of human beige adipocytes promotes the browning of fat (Kristóf et al, 2019). Moreover, irisin promotes the release of CXCL1 stimulated by human subcutaneous and neck differentiated adipocytes through upregulation of the NF-κB pathway (Shaw et al, 2021). However, whether the increase in IL-6 and CXCL1 in mothers has an effect on offspring adipocytes needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the myocardial infarction animal model, irisin treatment also shows myocardial protection, and better angiogenesis at the edge of infarction (Liao et al, 2019). Moreover, irisin can also stimulate adipocyte secretion of CXCL1 and improve endothelial cell adhesion (Shaw et al, 2021). Together, these results suggest that irisin has strong application value in promoting angiogenesis and improving the symptoms of ischemic diseases.…”
Section: Irisinmentioning
confidence: 85%